2, 4-Diarylamino-pyrimidines as kinase inhibitors co-targeting IGF1R and EGFRL858R/T790M. Issue 19 (1st October 2015) - Chan, Shingpan; Han, Kun; Qu, Rong; Tong, Linjiang; Li, Yingjun; Zhang, Zhang; Cheng, Huimin; Lu, Xiaoyun; Patterson, Adam; Smaill, Jeff; Ren, Xiaomei; Ding, Jian; et al.
Graphical abstract: Abstract: IGF1R amplification was recently implied to be related to the secondary acquired resistance against the 2nd or 3rd generation EGFR inhibitor therapies. We have successfully identified a series of 2, 4-diarylamino-pyrimidines as new IGF1R/EGFR L858R/T790M co-targeting agents. One of the most promising compounds8g potently inhibits both kinases with low nanomolar IC50 values, but is significantly less potent in inhibiting the wild type EGFR. The compound also displays a good kinase selectivity profile against a panel of 468 kinases. Moreover, 8g strongly suppresses the proliferation of CO-1686-resistant H1975-IGF1R cancer cells, suggesting its promising potential as a new lead compound for future anticancer drug discovery.